Effect of common table salt in improving the growth and survival of mud crab Scylla oceanica Dana, 1852 from first ZOEA megalopa stage - Santos, Francisco F. (Iloilo College of Fisheries, U. P. in the Visayas, 2000)
The study was conducted to determine the effect of adding common table salt (CTS) or solar dried seawater to the culture medium on the survival and growth of Scylla oceanica from first zoea (Z1) to megalope (M) stage. The newly hatched larvae were cultured at six different treatments by adjusting the salinity of culture media to 35 ppt with the addition of varying amount of salt : Treatment I (10 ppt + 29g/l CTS), Treatment II (15 ppt + 23 g/l CTS), Treatment III (20 ppt + 17g/l CTS), Tretament IV (25 ppt + 11g/l CTS), Tretament V (30 ppt + 5g/l CTS), and Treatment VI (35 ppt natural sawater, as control). Physiologically important ions like Na+, Cl-, Ca2+, K-, and Mg2+ were analyzed in each treatment.Treatment VI (control) gave the highest survival rate (26%), but it was not significantly different (P>0.05). Treatment V was significantlyhigher (P<0.05) than Treatment IV (13%). None of the larvae survived in Treatments I, II, and III after 1, 7, and 25 days of culture, respectively. Growth index values were highly significanamong treatments (P<0.01). Treatment VI gave the highest growth rate (6.0) followed by Treatment V (5.9), Treatment IV (5.7), and Treatment III (5.0). Complete metamorphosis to megalopa stage occurred on Day 25 at Treatment VI (control). For treatment V (30ppt + 5g/l) and TreatmentIV )IV )25 ppt + 11 g/l), almost all of the larvae metamorphosed to megalopa onDay 26. However, in Treatment III (20 ppt + 17 g/l) fifth zoea was attained on Day 22 but none of the larvae metamorphosed to megalopa stage. Culture media with higher concentrations ofCa2+ (949 to 1,264 mg/L), K- (27.141 to 41.497 mg/L), and Mg2- (2.7940 to 2.9299 mg/L) showed better survival, growth index values, and more number of megalopa produced than thosecultured in media with relatively lower concentration of Ca2- (663 to 783 mg/L), K- (8.238 to 21.476 mg/L), and Mg2- (2.5623 to 2.6852 mg/L). Correlation analysis showed that calciumpotassium, and magnesium contents in the medium were positively correlated with final percent survival. The final survival rate is directly related with Ca2- ions (y= -29.65 + 0.04294 * Ca2- ; r = 0.94544) ; K+ ions (y =-11.66 + 0.87056 * K+ , r = 0.94143) ; and Mg2- ions (y = -216.3 + 82.611 * Mg2-, r = 0.93041). Sodium and chloride ions were not correlated with treatments as their concentrations were not significantly different. The addition of common table salt (CTS) in diluted seawater does not give results comparable with natural seawater. Using CTS to raise the salinity of low saline waters could not compensate for the dilution of physiologically important ions at salinity 10, 15, and 20 ppt that are needed for survival and growth of Scylla oceanica larvae
Thesis (M. S. Fisheries-Aquaculture) -- Miagao, Iloilo : U. P. in the Visayas, January 2000.
Keywords: Mud crab; Scylla oceanica Dana, 1852.